A saúde mental por um fio de alta tensão: modelo de diagnóstico e de intervenção psicossocial sistêmica adotado em empresa do setor elétrico na gestão do absenteísmo. - Caldas, Laura Cândida Pedrosa (2016)
Describing the diagnosis and systemic psychosocial intervention model and the successful results at Energix1 is the general objective of this research and the specifics discussed in 06 articles: (01) to propose parameters for diagnosis of psychosocial risks in the work context and psychosocial intervention. system that supports the management of absenteeism and other People Management indicators; (2) to analyze the repercussions of absenteeism due to Mental and Behavioral Disorders (CMD) in workers and in the work context; (3) understand the psychosocial risks and harms to the mental health of the worker and the causal link of the work performed; (4) identify repercussions of TMC absenteeism on sick workers in the work context and financial impacts on Energix; (5) analyze the stratified statistical data of TCM absenteeism between 2010 and 2013, correlating them with the Statistical Yearbook of Accident at Work (AEAT-INSS, 2015); and (6) justify the inclusion of the psychologist in the Specialized Safety Engineering and Occupational Medicine Service (SESMT). Methods: literature review, epidemiological documentary research (Energix, 2010-2013) and triangulation of quantitative and qualitative methods (semi-structured interview, Work Inventory and Illness Risks (ITRA) and focus groups). Inclusion Criteria: Bibliographic, documentary and electronic searches on TMC absenteeism (1980-2014), workers with at least one day lost to work by TMC (2010-2013) and / or in management positions at Energix (2010-2013). Exclusion: publications outside the specified period, absenteeism for other pathologies, and employees who did not have TMC absenteeism and do not occupy management positions. Keywords: absenteeism, occupational health, psychosocial risk, mental health and work, CMD. Results: (1) the systemic psychosocial intervention model promotes collective speech space and enables successful interventions, contributing to the reduction of sick-absenteeism and business sustainability; (2) frequent research with nursing professionals; prevalent disorders: depression, anxiety and substance abuse; and damage of the economic-financial order to organizations and public coffers with social security benefits; (3) According to reports, the meaning of work, subjectivity, work organization and management mode generate psychosocial risks and are critical factors of symptomatology: emotionality, anxiety, anxiety, decreased libido, insomnia, stomach pain, hypertension. and bruxism; (4) impacts on workers with CMD: repercussions on family dynamics, colleagues and managers disbelieve the symptoms of psychic illness, financial loss, loss of chance and intensification of symptoms, with ideation and suicide attempt; impacts on work organization, peer relationship and people management; and Energix: cost based on the compensation / day of workers with absenteeism by TMC, between 2010 and 2013, in the amount of R $ 2,994,286.42; (5) TMC is sixth out of ten absenteeism groups at Energix and INSS is third; TMC commits 5.5% of the indicator while INSS does not reach 1%; and the prevalent CMD: mood disorders (depression), anxiety, stress-related neurotic, somatoform, adaptation and psychoactive substance use in INSS and Energix; and (6) psychological assessment can support the diagnosis of psychosocial risks and mental health problems. The psychologist's skills enable interventions and contribute to the management of absenteeism in the SESMT.